Towards identifying platinum anchor sites on carbon via a model electrochemical system - Fortuin, Adrian Charles (Department of Chemical Engineering, 2018)
The interaction between Pt and its carbon support was investigated by a model electrochemical system. This entailed aggressively oxidising a two-dimensional carbon substrate, i.e. highly orientated pyrolytic graphite (HOPG) and mirror finish graphite (MFG) quartz crystal, to incorporate oxygen terminated groups into the graphitic matrix. This study focusses on potential cycling to determine the mobility of Pt across these carbon surfaces and the effect of the Pt anchoring to carbon on the electrocatalyst durability. This work incorporates both a conventional three electrode electrochemical setup and the use of the electrochemical quartz crystal nano-balance (EQCN). The objectives of this study were to better understand the Pt mobility across the carbon substrate surface and to gain insight into the solid-liquid interface of Pt dissolution due to potential cycling. Initial results on HOPG as discussed in chapter 2, indicated minimal Pt dissolution of between 13% and 15% of total electrochemical active surface area loss. These results, however, did not provide adequate evidence to conclusively determine the extent of Pt mobility on the carbon surface and the effect of oxygen terminated groups in hindering Pt dissolution. In order to gain a more thorough understanding of the Pt dissolution processes, the use of the EQCN technique was utilised. Firstly, it was shown that the mirror finished graphite quartz crystals used in the EQCN technique, are qualitatively comparable to the electrochemical measurements recorded with the HOPG samples. Secondly, potential cycling under the same conditions as HOPG produced similar electrochemical results. The frequency response curves from the EQCN yielded the most promising results. This study showed, qualitatively, that the surface of Pt is non-monotonic, and that the surface charge changes with increased potential cycling. Pt/MFG-A had consistent frequency responses over the entire potential range during Pt dissolution, thus, with the above understanding of surface charge, it is concluded that acid treated carbon substrates show a stronger affinity for Pt anchoring.